Asymmetric Dearomatization of Indole by Palladium/PC‐Phos‐Catalyzed Dynamic Kinetic Transformation. (29th September 2020) - Chu, Haoke; Cheng, Jie; Yang, Junfeng; Guo, Yin‐Long; Zhang, Junliang
Abstract: A palladium‐catalyzed intermolecular dynamic kinetic asymmetric dearomatization of 3‐arylindoles with internal alkynes was developed with the use of achiral Xantphos and chiral sulfinamide phosphine ligand (PC‐Phos ) as the co‐ligands. This method could deliver various spiro[indene‐1, 3′‐indole] compounds in good yields (up to 95 % yield) with up to 98 % ee . The salient features of the transformation include the use of readily available substrates, ease of scale‐up and the versatile functionalization of the products. The mechanistic experiments gave some insights on active intermediates. Abstract : A palladium‐catalyzed intermolecular asymmetric dearomatization of 3‐arylindoles with internal alkynes was developed with the use of achiral Xantphos and chiral sulfinamide phosphine ligand (PC‐Phos) as the co‐ligands. This method could deliver various spiro[indene‐1, 3′‐indole] compounds in good yields (up to 95 % yield) with up to 98 % ee .